Pengaruh Virtual Laboratorium yang Terintegrasi dengan Mobile Game Edukasi Smartphone pada Praktikum Penentuan Senyawa Asam dan Basa - Rusdi, Hikmah; Lestari, Pertiwi Indah (Program Pasca Sarjana UNM, 2023)
This study aims to determine the effect of Virtual Laboratories Integrated with Mobile Educational Smartphone Games integrated virtual laboratories on learning outcomes in the practice of determining acid and base compounds. This type of research is a quasi-experimental with one group pretest posttest experimental design. The sample of this study were 10 semester 1 students who were determined by the simple total technique. The instrument used in this research is the learning achievement test. The results of data analysis can be concluded that there is an effect of virtual laboratories on student learning outcomes with a sig (2-tailed) value less than 0.05 (0.000 <0.05).